O Fenômeno desinformação sob a perspectiva dos arquivistas brasileiros - OLIVEIRA, Jenifer Galdino de (2022)
The present research aimed to understand the perception of archivists about the phenomenon Disinformation and the role of Information Literacy in this interaction. Therefore, a bibliographic and statistic research was used as methodology, and for data collection a questionnaire was used as ressearch instrument was used to obtain the necessary elements for this study. From the data analysis, it was possible to consider the perception of archivist professionals about the phenomenon Disinformation and identify the effects that this phenomenon may cause on their performance. Finally, through the research, it was observed that archivists understand disinformation as much as recognize that their performance may be affected by this phenomenon, as well as understand the importance of developing new skills to deal with the impacts of disinformation on their practices.